Determining internal leakages of high pressure and temperature steam valves - Bapeekee, Sulaiman Ahmed Sadeck (Department of Mechanical Engineering, 2017)
Internal leakages of high pressure and temperature steam valves have been identified as a potential contributor to a loss in power generating plant efficiency. These losses are often neglected due to it being difficult to detect problematic valves and quantify the internal leakages through them. A non-intrusive NOT technique that detects and quantifies internal leakages through valves will be a very favourable tool to any power generating plant as it will allow for the early detection of internal leakages and could possibly provide considerable financial savings. This research evaluates different monitoring techniques suitable for detecting and quantifying internal leakages through valves and selects a technique that is most suitable for application in a power generating plant environment. The proposed technique utilises infra-red thermography to calculate pipe surface temperatures on a length of un-insulated pipe located downstream of a valve that is leaking internally. As the leakage steam flows through the length of un-insulated pipe, it will lose a portion of its heat energy through the pipe wall to the surrounding environment. This will result in a drop in temperature of the steam from the upstream to downstream points of the un-insulated length of pipe. By calculating the heat loss and the drop in temperature of the leakage steam, a mass flow rate of the leakage steam can be determined. A mathematical model was derived which with inputs of upstream and downstream pipe surface temperatures of the un-insulated pipe, pipe properties and ambient air conditions, calculates the heat loss, the temperature drop and the resulting mass flow rate of the leakage flow through the valve. A detailed experimental study was conducted to validate the proposed technique in determining internal leakages thought steam valves. Steam generated from a mini steam generating plant was allowed to flow through an experimental test rig, which contained a length of un-insulated pipe, at different flow rates. Pipe surface temperature measurements of the un-insulated pipe were made using an infrared thermal camera and a mass flow rate of the steam was calculated using the derived mathematical model. In all experiments, the mass flow rate calculated using the mathematical model was compared to a mass flow rate acquired from a flow measuring device installed in-line with the experimental test rig. The results indicate that an increase in mass flow rate causes an increase in pipe surface temperatures of the un-insulated pipe which translates to an increase in heat loss of the leakage steam through the length of un-insulated pipe. The mass flow rate calculated using the proposed technique closely approximates the mass flow rate acquired from the flow measuring device. This indicates that the proposed technique, using infrared thermography, is capable of detecting and quantifying possible internal valve leakages encountered in online operation. Onsite tests were performed using the proposed technique on two different boiler drain valves at Majuba Power Station. It was found that one of the valves was internally leaking steam to the atmosphere at a rate of 0.039 kg/s whilst the other valve was sealing correctly. A comprehensive financial impact study was conducted, and it was found that this leakage steam will result in a total loss of R 730 108 per annum if the leak is left unattended. This is the loss for a single valve that has a relatively small leak. The financial loss for a combination of all valves that are internally leaking in a power plant could be substantial and can clearly justify plant personnel in utilising the proposed technique to identify problematic valves. With its portability, non-intrusiveness and ease of use the proposed technique provides a cost-effective means to determine internal leakages through power plant valves.